Numerical Modelling of Steam Superheaters in Supercritical Boilers - Katarzyna Węglarz; Dawid Taler; Jan Taler; Mateusz Marcinkowski (Energies, 2023)
This paper presents a numerical model of a four-pass supercritical steam superheater with a complex flow system. The specific heat of steam is a function of temperature and pressure, and the specific heat of flue gas is a function of temperature. Pressure and temperature changes along the length of the tubes were also determined. The modified Churchill equation was used to calculate the steam-side friction factor of Darcy–Weisbach. The flue gas temperature variations behind the individual superheater tube rows were calculated. The steam and wall temperature distributions were determined in each tube row along its length. Knowing the temperature of the tube walls and the steam along the flow direction enables the selection of the correct steel grade for the tubes. Thanks to this advantage of the proposed method, the investment can be reduced in superheater construction without the danger of overheating the tube material. The results of the superheater simulation were compared with the results of measurements on the actual object. The proposed numerical method can find application in steam superheaters’ design and performance calculations. It can also be used to monitor superheater operating parameters, which are difficult to measure due to the high flue gas temperature.